The mitochondrial and death receptor pathways involved in the thymocytes apoptosis induced by aflatoxin B(1) - Peng, Xi (Oncotarget, 2016)
Aflatoxin B(1) (AFB(1)) is a potent immunosuppressive agent in endotherms, which can be related to the up-regulated apoptosis of immune organs. In this study, we investigated the roles of the mitochondrial, death receptor, and endoplasmic reticulum pathways in Aflatoxin B(1) induced thymocytes apoptosis. Chickens were fed an aflatoxin B(1) containing diet (0.6 mg/kg AFB(1)) for 3 weeks. Our results showed that (1) AFB(1) diet induced the decrease of T-cell subsets, morphological changes, and excessive apoptosis of thymus. (2) The excessive apoptosis involved the mitochondrial pathway (up-regulation of Bax, Bak, cytC and down-regulation of Bcl-2 and Bcl-xL) and death receptor pathway (up-regulation of FasL, Fas and FADD). (3) Oxidative stress, an apoptosis inducer, was confirmed in the thymus. In conclusion, this is the first study to demonstrate that mitochondrial and death receptor pathways involved in AFB(1) induced thymocytes apoptosis in broilers.